“Evaluación de indicadores productivos en dos líneas de hembras broilers con dos sistemas de alimentación en condiciones del trópico” - Moreira Arriaga, Erick Stalyn (2019)
Summary The experimental work is carried out to analyze the productive factors such as weekly weight, feed consumption and feed conversion, using 400 female broilers 200 of the Cobb 500 line and 200 of the Ross 308 line in two ships in uncontrolled times, the birds for the distributed study randomly distributed in both sheds with the purpose of the homogeneous sea the influence of the interactions with its factors such as temperature, feeding and lines (Cobb 500 and Ross 308).